2015
DOI: 10.1021/acs.jpcc.5b07253
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of H2, CO2, and Their Mixtures in the Porous Zirconium Based Metal–Organic Framework MIL-140A(Zr): Combination of Quasi-Elastic Neutron Scattering Measurements and Molecular Dynamics Simulations

Abstract: The diffusivity of H 2 and CO 2 in the small pore Zr based metal−organic framework (MOF) MIL-140A(Zr) has been evaluated using a combination of quasi-elastic neutron scattering measurements and molecular dynamics simulations. These two techniques were used to determine the self-diffusivities of H 2 , and the corrected and transport diffusivities of CO 2 , as single components and binary mixture. H 2 was shown to be the faster of the two gases to diffuse through the narrow triangular channel of MIL-140A(Zr), it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 89 publications
0
27
0
Order By: Relevance
“…Consequently,t his renders questionable the isotropic force fields commonlyu sed for dynamical computations of CO 2 capture in nanoporous MOFs/ZIFs and of CO 2 -Zn enzyme activity. [60] Indeed, our calculations showt hese potentials become close to isotropic only if CO 2 is far away (more than 2)f rom Im andn ot where it is attached( i.e.,e quilibrium). Moreover, stereodynamical and orientation effects are expected to occur if CO 2 is present in ac onfined nanopore environ- www.chemphyschem.org ment.…”
Section: Site Selectivitymentioning
confidence: 67%
See 1 more Smart Citation
“…Consequently,t his renders questionable the isotropic force fields commonlyu sed for dynamical computations of CO 2 capture in nanoporous MOFs/ZIFs and of CO 2 -Zn enzyme activity. [60] Indeed, our calculations showt hese potentials become close to isotropic only if CO 2 is far away (more than 2)f rom Im andn ot where it is attached( i.e.,e quilibrium). Moreover, stereodynamical and orientation effects are expected to occur if CO 2 is present in ac onfined nanopore environ- www.chemphyschem.org ment.…”
Section: Site Selectivitymentioning
confidence: 67%
“…This work can be generalized to help understanding the adsorptiono fC O 2 at open metal sites in microporous materials and biological entities and to establish the adsorption mechanisms, sites and dynamics of these gases in such porousm aterials. [60,63] Moreover,t his work establishes that CO 2 interaction with organozinc compoundss lightly affectst he Zn structure and environment. Similar CO 2 @[Zn q + Im] structures are found if the oxidation degree of Zn is changed.…”
Section: Discussionmentioning
confidence: 95%
“…Particular emphasis was placed on the mechanisms underlying the diffusion of molecules in confined pores of the hybrid material using Molecular Dynamics, a strategy that we have intensively applied over the last decades to explore the diffusion of a series of gases in various MOFs. [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]…”
Section: Introductionmentioning
confidence: 99%
“…The unusual dynamics of water and other molecules under confinement has been subject to several experimen-tal and theoretical studies (Tan et al 2005;Sendner et al 2009;Su and Guo 2011;Nguyen and Bhatia 2012;Bourg and Steefel 2012;Srivastava et al 2012;Xu et al 2013;Planchais et al 2014;Prakash et al 2015;Han et al 2015;Qiu and Huang 2015;Nie et al 2016). In particular, nuclear magnetic resonance (NMR) techniques showed that water diffuses anisotropically inside nanoporous systems (Cleve-land et al 1976;Thomsen et al 1987;Wei et al 2011;Salles et al 2011) and two different self-diffusion coef-ficients of water were measured in sheep Achilles tendon using pulsed-field-gradient stimulated-echo NMR (Fechete et al 2005).…”
Section: Introductionmentioning
confidence: 99%